2018
DOI: 10.3341/kjo.2018.0008
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Intraocular Lens Power Calculation Methods Following Myopic Laser Refractive Surgery: New Options Using a Rotating Scheimpflug Camera

Abstract: PurposeTo evaluate and compare published methods of calculating intraocular lens (IOL) power following myopic laser refractive surgery.MethodsWe performed a retrospective review of the medical records of 69 patients (69 eyes) who had undergone myopic laser refractive surgery previously and subsequently underwent cataract surgery at Samsung Medical Center in Seoul, South Korea from January 2010 to June 2016. None of the patients had pre-refractive surgery biometric data available. The Haigis-L, Shammas, Barrett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 26 publications
1
21
0
4
Order By: Relevance
“…We suggest that if the Haigis-L or Shammas-PL could be obtained, these formulae would be better than the Double-K method. Previous studies have shown that the Double-K method had good predictability of IOL power calculation when refractive historical data was known, but its accuracy decreased when historical data was unknown [17,29]. In addition, when we included Cho et al's 2018 study, I 2 was 54% and there was no significant difference between Haigis-L and Shammas-PL (P = 0.34, Fig.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…We suggest that if the Haigis-L or Shammas-PL could be obtained, these formulae would be better than the Double-K method. Previous studies have shown that the Double-K method had good predictability of IOL power calculation when refractive historical data was known, but its accuracy decreased when historical data was unknown [17,29]. In addition, when we included Cho et al's 2018 study, I 2 was 54% and there was no significant difference between Haigis-L and Shammas-PL (P = 0.34, Fig.…”
Section: Discussionmentioning
confidence: 79%
“…Among these, three studies did not have percentage data, 16 studies included only one of the selected formulae, five studies were hyperopic laser refractive surgery or radial keratotomy surgery. After the exclusion of these studies, 16 articles were used for analysis [5,[12][13][14][15][16][17][22][23][24][25][26][27][28][29][30].…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, cataract surgery may present possible postoperative complications such as corneal decompensation [3], the possibility of a cornea with more swelling [4], anterior chamber reaction [5], cystoid macular edema [6], increased intraocular pressure, and, rarely, endophthalmitis [7]. An objective approach to preoperative evaluations is required to obtain the best results [8].…”
Section: Introductionmentioning
confidence: 99%
“…Before 2014, the accuracy of the Haigis-L, Shammas-PL, and W-K-M formulas was comparable, and the Double K method was slightly lower than the other three formulas [12]. After that, a large number of studies have shown that the accuracy of the Haigis-L is comparable to that of the Shammas-PL formula, while the W-K-M and Double K formulas are less accurate [17,27]. But in our analysis, there is no statistically significant difference in the percentage of refractive error percentage of the above four formulas, only the Haigis-L has better percentage of refractive predicted error within ±1.0D than the W-K-M method.…”
Section: Discussionmentioning
confidence: 98%